2017
DOI: 10.1117/1.jrs.11.036011
|View full text |Cite
|
Sign up to set email alerts
|

Toward an operational framework for fine-scale urban land-cover mapping in Wallonia using submeter remote sensing and ancillary vector data

Abstract: Eléonore Wolff, "Toward an operational framework for fine-scale urban land-cover mapping in Wallonia using submeter remote sensing and ancillary vector data," J. Appl. Remote Sens. 11(3), 036011 (2017), doi: 10.1117/1.JRS.11.036011. Abstract. Encouraged by the EU INSPIRE directive requirements and recommendations, the Walloon authorities, similar to other EU regional or national authorities, want to develop operational land-cover (LC) and land-use (LU) mapping methods using existing geodata. Urban planners and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Consequently, colour infrared aerial photos are conventionally regarded as unfit for image transformation and index calculation and we have not found that they have been used to assess primary productivity before. Still, colour infrared aerial orthophotos are increasingly used to automatically separate vegetation from non-vegetation (Banzhaf and Hofer 2008;Grafius et al 2016;Beaumont et al 2017). If it would be possible to use the information contained in the colour infrared aerial photos to obtain some assessment of primary productivity it could provide a fruitful way to investigate vegetation over regional areas of several square km with a high spatial resolution, especially in areas with low-satellite coverage.…”
Section: Technical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, colour infrared aerial photos are conventionally regarded as unfit for image transformation and index calculation and we have not found that they have been used to assess primary productivity before. Still, colour infrared aerial orthophotos are increasingly used to automatically separate vegetation from non-vegetation (Banzhaf and Hofer 2008;Grafius et al 2016;Beaumont et al 2017). If it would be possible to use the information contained in the colour infrared aerial photos to obtain some assessment of primary productivity it could provide a fruitful way to investigate vegetation over regional areas of several square km with a high spatial resolution, especially in areas with low-satellite coverage.…”
Section: Technical Backgroundmentioning
confidence: 99%
“…; Beaumont et al. ). If it would be possible to use the information contained in the colour infrared aerial photos to obtain some assessment of primary productivity it could provide a fruitful way to investigate vegetation over regional areas of several square km with a high spatial resolution, especially in areas with low‐satellite coverage.…”
Section: Introductionmentioning
confidence: 97%
“…It could be used on a highperformance computing system to distribute the work on hundreds of different nodes. In this regard, a comparison with eCognition® rule-based classification highlighted the flexibility of the open-source framework in terms of perspective for further developments [13].…”
Section: Big Data and Automation For Object-based Land Cover Mappingmentioning
confidence: 99%
“…Such inventory reports have to provide information regarding land identification for estimating change in carbon stock. According to [2] definitions, GHG emissions are estimated through the classification of the land into six LU categories: (1) forest land, (2) cropland, (3) grassland, (4) wetlands, (5) settlements, and (6) other land. Only broad and nonprescriptive definitions are provided for these LU categories: Countries may use their own definitions, which may or may not refer to internationally accepted definitions.…”
Section: Introductionmentioning
confidence: 99%
“…The current LULC map of Wallonia (Carte d'Occupation des sols de Wallonie (COSW)) dates from 2007 and is based on a combination of several data sources such as a cadastral plan and agricultural census. According to Reference [4], the LULC map of Wallonia relies on outdated, mixed, and incomplete LC and LU information. For this study, we were looking for an approach that would integrate data available at the European scale (i.e., not regional datasets) and be updatable on an annual basis.…”
Section: Introductionmentioning
confidence: 99%